A Fresh Evidence of Income Inequality and Health Outcomes Asymmetric Linkages in Emerging Asian Economies - Chang, Shuangshuang; Gao, Bin (Frontiers in Public Health, 2021)
During the last few decades, income inequality in emerging Asian economies has been increased dramatically. It is widely recognized that income inequality has severely impacted population health. This study attempts to estimate the impact of income inequality on health outcomes in emerging Asian economies for a time horizon ranging from 1991 to 2019. Our empirical analysis shows that income inequality has a negative effect on life expectancy in the long run. We also find that positive changes in income inequality decrease life expectancy, but a negative change in income inequality increases life expectancy in the long run in emerging Asian economies. The symmetric and asymmetric results are robust to different measures of econometric methods. Thus, governments should pay more attention to the consequences of their economic policies on income inequality to improve health outcomes.